2015
DOI: 10.1016/j.apenergy.2014.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on firms’ electricity demand: An analysis of sectorial differences in Spain

Abstract: Global warming, intermittent production, and efficient use of energy require adequate demand response policies. The price inelasticity of electricity demand represents the main obstacle for developing adequate measures. A potential source of demand inelasticity is the temperature effect -the reaction of electricity demand to variations in temperature. Studies using aggregate data show that temperature-driven electricity demand is growing in most countries. Using disaggregated data by sectors, we analyze the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…So, with any rise or fall of the air temperature, consumers begin to use air conditioners, and they may violate their obligations in DR and EE programs. [49][50][51] A reduction in the selected capacity of consumers implies that retailers may fail to fulfill their commitments in the capacity market and will be penalized. So retailers should predict this capacity reduction and participate in the capacity market based on their available capacity.…”
Section: Modeling Of Air Temperature Change (Modeling Of For 1 )mentioning
confidence: 99%
“…So, with any rise or fall of the air temperature, consumers begin to use air conditioners, and they may violate their obligations in DR and EE programs. [49][50][51] A reduction in the selected capacity of consumers implies that retailers may fail to fulfill their commitments in the capacity market and will be penalized. So retailers should predict this capacity reduction and participate in the capacity market based on their available capacity.…”
Section: Modeling Of Air Temperature Change (Modeling Of For 1 )mentioning
confidence: 99%
“…It is observed that short cycling electricity consumption is significantly influenced by day type (such as weekday, weekend, official holiday, religious days) and weather conditions. It is seen that meteorological variables such as temperature, precipitation and humidity are influential in the regional consumption of electricity and the meteorological variable which is the most effective is the temperature [4]. Slide.…”
Section: Introductionmentioning
confidence: 99%
“…), appliances, building typehowever the effect of abovementioned is not completely understood [2]. According to many research papers which has been assessed by [4] the temperature which is understood usually as cooling and heating degree-days (CDD, HDD) poses a strict influence on electric energy demand in case of residential sector. However, as other studies pointed out this situation may prevail only for some sectors and even if, its range may be limited to the selected region.…”
Section: Introductionmentioning
confidence: 99%
“…However, as other studies pointed out this situation may prevail only for some sectors and even if, its range may be limited to the selected region. Authors [4] state that in case of Spain there is a total lack of industrial activities electricity demand to the temperature variation.…”
Section: Introductionmentioning
confidence: 99%